Responses in the brain of estrogen receptor α-disrupted mice - Shughrue, Paul J. (The National Academy of Sciences of the USA, 1997)
These studies sought to determine if neurons in the estrogen receptor-α knockout (ERαKO) mouse brain concentrated 16α-[(125)I]iodo-11β-methoxy-17β-estradiol ((125)I-estrogen), and if so, whether estrogen binding augmented the expression of progesterone receptor (PR) mRNA. Mice were injected with (125)I-estrogen and cryostat sections thaw mounted onto emulsion-coated slides. After 30–90 days of exposure, cells with a nuclear uptake and retention of (125)I-estrogen were observed in a number of ERαKO mouse brain regions including the preoptic nucleus and arcuate nucleus of the hypothalamus, bed nucleus of the stria terminalis, and amygdala, although the number of labeled cells and intensity of nuclear concentration was markedly attenuated when compared with wild-type littermates. Competition studies with excess 17β-estradiol, diethylstilbestrol, or moxestrol, but not with R5020 or dihydrotestosterone, prevented the nuclear concentration of (125)I-estrogen. To determine if the low level of estrogen binding was capable of regulating gene expression, in situ hybridization was used to evaluate PR mRNA in the brain. ERαKO and wild-type mice were ovariectomized and treated with vehicle or 17β-estradiol, and brains were sectioned and hybridized with a PR cRNA probe. Analysis of hybridization signal revealed a similar, low level of PR mRNA in ovariectomized wild-type and homozygous mice, and a marked increase in expression after treatment of ovariectomized animals with 17β-estradiol, with the level of hybridization signal being significantly higher in wild-type animals when compared with ERαKO mice. The results demonstrate that estrogen binds in the ERαKO brain and is capable of modulating PR gene expression, thus supporting the presence and functionality of a nonclassical estrogen receptor.